A Pedagogy of Play: Reasons to be Playful in Postsecondary Education. (September 2021) - Leather, Mark; Harper, Nevin; Obee, Patricia
Background: Teaching experientially in postsecondary education has challenges; institutional constraints, neoliberal management, and a colonized learning environment. We discuss playing as a form of experiential education.Purpose: We challenge conventional teaching and offer an alternative to enrich and broaden conventional pedagogies. We argue for the benefits of playfulness and how this leads to creativity, wellness, and improved graduate employability.Methodology/Approach: As provocation to the consequences of neoliberalism in education, we examine the literature from a biased position as advocates of play and experiential education. We argue for faculty to adopt an ontology and pedagogy of play.Findings/Conclusions: Play is well represented in the literature; contributing positively to a range of health and educational outcomes. As play manifests in numerous forms in postsecondary education, faculty would benefit from a clear educational rationale for an ontology and pedagogy of play. We share examples from our practice which highlight spontaneous and planned play and playful attitudes/behaviors and suggest how play may be integrated as planned curriculum.Implications: Ideally, these concepts resonate with faculty allowing them to challenge conventional pedagogies and confirm play in practice with the underpinning of experiential education research.